Biochemical and Pathogenic Characterization of Rhizobacteria with Insecticidal Activity Against Spodoptera litura - Yaumil Khairiyah; Maulidi Firlandiana; Siti Mudrikah; Rizky Estiningtyas; Iwan Perala; Intan Nirmalasari; Rifki Rahmatullah (Institut Pertanian Bogor, 2026)
The increasing demand for environmentally friendly alternatives to chemical pesticides has driven the exploration of rhizosphere bacteria as biocontrol agents. The rhizosphere is recognized as a hotspot for functionally diverse bacteria with biocontrol potential owing to intense plant-microbe interactions and selective ecological pressures. This study successfully isolated and characterized thermotolerant bacteria from acidic long bean and soybean soils to control the armyworm pest Spodoptera litura. Sixteen bacterial isolates were obtained through serial dilution and temperature selection (28°C to 90°C), two of which, KP284 and K504a, demonstrated potent entomopathogenic activity. These isolates induce rapid larval mortality (wet-lysis type) within 2–5 days after ingestion, which is a distinct and effective mode of action. Biochemical profiling revealed that both isolates were gram-negative, obligate aerobes, catalase- and oxidase-positive, with strong acid production during carbohydrate fermentation, and capable of growing under acidic to neutral pH conditions. Importantly, both isolates were non-pathogenic to plants and animals, ensuring their safety. Furthermore, the bacteria maintained viability in low-cost organic carrier media (molasses and rice washing water), supporting the formulation of a practical biopesticide. These findings highlight KP284 and K504a as promising candidates for sustainable pest management in tropical agriculture, representing a novel contribution to rhizobacterial biocontrol research. Keywords: biochemical test, biopesticides, KP284, organic carrier formulation, thermotolerant rhizobacteria